PERBANDINGAN METODE PENGAJARAN TRADISIONAL DAN MODERN DALAM PENDIDIKAN AGAMA ISLAM: Studi di Lembaga Pendidikan Internasional ABFA Pamekasan - Supandi, Supandi; Subhan, Mohammad; Hobir, Abdul (Dewan Pendidikan Pamekasan, 2024)
This research investigates comparing traditional and modern teaching methods in Islamic religious education at the ABFA Pamekasan International Education Institute. Traditional teaching methods are characterized by an authoritative approach that emphasizes the teacher's role as the main source of knowledge. In contrast, modern teaching methods emphasize interactivity, collaboration, and the use of technology to increase student involvement in learning. This research method uses a comparative qualitative approach by observing classes that apply both teaching methods, conducting interviews with teachers and students, and analyzing educational documents such as lesson plans. Data were analyzed to identify the effectiveness of each method in facilitating a deep understanding of Islamic religious teachings and student responses to learning. The main findings show that modern teaching methods tend to be more effective in increasing student engagement and facilitating an applicable understanding of Islamic religious values. Students respond positively to interactive approaches and the use of technology in learning. However, challenges such as access to technology and local cultural context also influence the implementation of effective teaching methods. The results of this research significantly contribute to the development of Islamic teaching strategies in modern educational environments, by emphasizing the importance of adapting teaching methods according to student needs and prevailing traditional values. The practical implications of this research can help improve the quality of Islamic religious education at the ABFA Pamekasan International Education Institute and the like.